A new genus, Sinodromus gen. nov., with two new species and the first description of the female of Philodromus guiyang Long & Yu, 2022 (Arachnida, Araneae, Philodromidae) from China - Zhong-jing Wang; Yan-bin Yao; Zi-ying Tang; Wen-hui Li; Ke-ke Liu; Xiang Xu (ZooKeys)
Three species of the spider family Philodromidae are reported from the south of China. A new genus, Sinodromus gen. nov., is described from Jiangxi, Fujian, and Hunan Provinces. It can be distinguished from other genera of Philodromidae by the tegular apophysis of the palp and the cymbial process, as well as by its uniquely striped abdomen. The type species, S. fujianensis sp. nov., and a second species, S. perbrevis sp. nov., are described and illustrated; these species occur in bamboo forests in hilly areas. Additionally, the female of Philodromus guiyang Long & Yu, 2022 is described for the first time from Jiangxi and Hunan Provinces. All species are illustrated with SEM micrographs, and their distributions are mapped.